COMMON FIXED POINT RESULTS FOR GENERALIZED CYCLIC CONTRACTION PAIRS INVOLVING CONTROL FUNCTIONS ON PARTIAL METRIC SPACES - Mohanta, S. K.; Biswas, P. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2021)
In this paper, our purpose is to establish some coincidence point and common fixed point results for a pair of self mappings satisfying some generalized cyclic contraction type conditions involving a control function with two variables in partial metric spaces. Moreover, we provide some examples to analyze and illustrate our main results.